Capitalism, health and wellbeing : rethinking economic growth for a healthier, sustainable future - Noonan, Rob (Emerald Publishing Limited, 2024)
Health inequalities are widening, and crises of obesity, physical inactivity and mental health are worsening around the world. Yet there remains a reluctance to discuss the threat capitalism poses to health and wellbeing. Offering a unique contribution to the field, Capitalism, Health and Wellbeing: Rethinking Economic Growth for a Healthier, Sustainable Future addresses the elephant in the room: economic growth. Challenging this crucial yet overlooked issue, author Rob Noonan contends that the drive for economic growth is at odds with the United Nations' Sustainable Development Goals to achieve a better and more sustainable future. He argues that if the 'health for all' goal is to be achieved, it is imperative to redesign the economic system and social progress metrics that promote productivity and consumption at the expense of health and wellbeing. While clearly outlining the challenges governments face, Noonan offers solutions on how we can reverse the accelerating trends of obesity, physical inactivity and poor mental health, as well as how we can use scientific understanding and history to improve public health and reduce health inequalities. Rooted in thoughtful evidence and achievable actions, this work empowers readers to contribute to positive transformation and create a healthier, more just and more sustainable world.
Includes index.
Keywords: Medical economics.; Capitalism.; Economic development.; Popular medicine and health: the human body.; elektronické knihy; electronic books